FENOMENA IT’S A DRESS NOT A YES DALAM POLEMIK RUU TENTANG KEKERASAN SEKSUAL DI INDONESIA (ANALISIS UNGGAHAN INSTAGRAM AGRI MERINDA DENGAN KACAMATA STRUKTURALISME- KONSTRUKTIF PIERRE BOURDIEU) (Jurnal Nawala Politika, 2023)
ABSTRACT This research attempts to trace the emergence of the It’s A Dress Not A Yes phenomenon in Indonesia through Agri Merinda’s activism in her Instagram uploads. The researcher wants to analyze the form of Agri Merinda’s activism related to this phenomenon in the polemic context of Sexual Violence’s Draft Law in Indonesia. This research uses the structuralism-constructive theory of Pierre Bourdieu, thus theory is important to explored emergence of Agri Merinda’s activism using concepts such as habitus, field, capital, and doxa which consists of heterodoxy and orthodoxy. This research uses the non-participant observation method, with research results: firstly, the emergence of Agri Merinda’s activism related to It’s A Dress Not A Yes phenomenon can be traced through the history of her education and experiences. The success of Agri Merinda’s habitus emerged through the accumulation of her capitals. Secondly, this research has answered the position of It’s A Dress Not A Yes phenomenon in the polemic of Sexual Violence’s Draft Law in Indonesia. Keywords: It’s A Dress Not A Yes, Polemic, Instagram Uploads